Resident’s personality traits on acceptance of information system: Case study of Majlis Perbandaran Sungai Petani (MPSPK) - Mohd Zool Hilmie, Mohamed Sawal (2021)
The rapid development of information technology nowadays has changed the way we live and work significantly. Malaysia is actively improving its infrastructure as a way to give the best services to its local community. As to date, the local government is working on improvising their services to the local community via information system. Thus, the people’s acceptance towards information system is important in ensuring the success of the local government’s objective in providing better and efficient services. This research is based on Big Five Personality Trait as the underpinning model. This study attempts to identify the personality patterns of the community who uses the information system that has been introduced by their local government. In addition to that, this study also intends to unravel the relationship between local community’s beliefs and personality patterns. Through this study, problems faced by users regarding the information system are also analysed. The research findings were derived from quantitative and qualitative methods based on the data collection process using questionnaires involving 355 respondents and face to face interviews with eight (8) local community and four (4) local government officers. The findings indicate mixed results in answering the research objectives. The findings have shown that each person's personality patterns are different in giving opinions and expectations from their local government. The element of trust plays an important role in ensuring the success of information systems. However, when each personality is being analysed, the result indicates extraversion, agreeableness and conscientiousness produced negative feedback. Based on the findings, several recommendations are made such as monitoring and evaluation of the program, awareness program and empowering the community with suitable and relevant knowledge. These can assist the local government to improve their services towards local community.